Capacity Building of Majalaya Village through Training on Designing Flood Detection Systems for Village Youth in an Effort to Mitigate Flood Disasters - Pramudita, Resa; Fauzan, Mochamad Rizal; Purnama, Wawan; Rizqulloh, Muhammad Adli; Ardiansyah, Neris Peri; Pawinanto, Roer Eka (Institut Teknologi Nasional, Bandung, 2024)
Flooding remains a significant issue in Majalaya Village, Bandung Regency, West Java, due to its geographical location near the Citarum River. This community service project aimed to enhance disaster mitigation efforts by training village youth to design and implement a flood detection system. The system utilized ESP32 microcontrollers, infrared sensors, and solar-powered technology to provide early flood warnings. Through a structured training program, participants gained practical skills in assembling, installing, and maintaining the system. The project emphasized community ownership, ensuring sustainability and fostering collaboration among local stakeholders. Evaluation results indicated high participant satisfaction and confidence in system operation, though follow-up support is recommended for long-term success. The initiative serves as a potential model for other flood-prone regions seeking community-driven disaster mitigation solutions.